(untitled) (Encuentros, 2016)
This research[1] aims to identify communication factors that help in the development of markets for young people. To accomplish this, we use instrumental variables that closely relate to communication with young people from Villavicencio: direct marketing, promotion, sales, public relations, advertising and digital media. Using SPSS, we present data in two blocks. The first corresponds to the analysis of all the young people in the city while the second makes a comparison between young people from low socio-economic level with those in medium to high levels.